Evaluation of Esthetics on Fixed Implant Supported Prosthesis - M - Rismanchian; M Jaffari; S Mahdevi (Isfahan University of Medical Sciences, 2005)
Introduction. Nowadays dental implants are accepted as a successful replacement of conventional fixed and removable prosthesis which can restore esthetics in an ideal way. Because of visibility of anterior teeth while smiling and speaking, the importance of esthetics in these areas is very important. In this research, the provision rate of esthetic indexes of crowns supported with swiss- plus implants is assessed, also overall patient satisfaction is evaluated.Methods. The study was done on 21 patients who were treated with 30 implant supported crowns and the variables: clinical crown length , crown width , faciolingual dimention of crown, contact point position, soft tissue margin level and papilla index, crown color, abutment visibility and patient satisfaction range were assessed. Differences in variables between two groups were analyzed using the paired t- test. A wilcoxon signed rank test was used in analysis of differences in papilla index score.Results. The average amount indexes in implant-supported crowns and natural teeth in arrangement were: clinical crown length 10.05mm and 9.35mm, crown width 7.36mm and 7.33mm, faciolingual dimension 6.67mm and 7.72mm, mesial contact point position 36.20 and 32.86 percent, distal contact point position 50.86 and 41.76 percent, soft tissue margin level -0.64mm and -0.15mm, papilla index in mesial 2.17mm and 2.60mm, papilla index in distal 2.10mm and 2.63mm. color of 24 crowns were similar to natural teeth and in one case abutment was visible. 95.2 percent of patients expressed satisfaction from esthetics of the crowns (60 percent complete satisfaction and 40 percent partial satisfaction).Discussion. In comparison to the natural teeth, The crowns 1 were longer 2 had smaller faciolingual width 3 had more apically soft tissue margin level 4 had lower scores of papilla index. No significant statistically differences were observed in mesiodistal width and contact point position between two groups.Key words. Esthetics, Fixed implant-supported crowns, Swiss-plus, Soft tissue, Satisfaction